2006
DOI: 10.1200/jco.2005.03.7184
|View full text |Cite
|
Sign up to set email alerts
|

Additional Genetic High-Risk Features Such As 11q Deletion, 17p Deletion, and V3-21 Usage Characterize Discordance of ZAP-70 and VH Mutation Status in Chronic Lymphocytic Leukemia

Abstract: There were characteristic modes of discordance between ZAP-70 and VH mutation status depending on the presence or absence of additional genetic high-risk features such as 11q and 17p deletion or V3-21 usage. Although the biologic background for these findings is yet to be determined, these data have biologic and clinical implications regarding ZAP-70 as a pathogenic factor and outcome predictor, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
126
3
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(145 citation statements)
references
References 32 publications
12
126
3
4
Order By: Relevance
“…In our study it was also found that there was a very good correlation between ZAP-70 expression and IgV H mutations and, not surprisingly, that ZAP-70 had a prognostic value equivalent to that of IgV H mutations (20). Afterwards, many other groups have reproduced these results (20,22,(25)(26)(27)(28)(29)(30) (Tables 1 and 2). The reasons for discrepant cases, which range from 8 to 25%, are not fully understood.…”
Section: Zap-70 Expressionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our study it was also found that there was a very good correlation between ZAP-70 expression and IgV H mutations and, not surprisingly, that ZAP-70 had a prognostic value equivalent to that of IgV H mutations (20). Afterwards, many other groups have reproduced these results (20,22,(25)(26)(27)(28)(29)(30) (Tables 1 and 2). The reasons for discrepant cases, which range from 8 to 25%, are not fully understood.…”
Section: Zap-70 Expressionsupporting
confidence: 73%
“…The various reports, however, differ in the methods used to determine ZAP-70 expression. Recently, Krober et al have shown that unmutated CLL cases with high expression of ZAP-70 frequently present other biological features such as del(17p) conveying poor prognosis (27).…”
Section: Zap-70 Expressionmentioning
confidence: 99%
“…Mean and SEM of 18 individual CLL samples measured in duplicate or triplicate (samples no. 2,6,8,15,17,18,19,21,24,28,33,36,39,40,41,43,48,50) are shown; **p < 0.001; *p < 0.05; (right) Graph illustrates specific cell death upon treatment with 10 mM Fludarabine or BV6 of genomic subgroups including norm/13q-, IGVH non-mutated, tp53 mutated and 17p deletion. (e and f) BV6-sensitive primary CLL cells were co-treated with 10 mM BV6 and 1,000 ng/ml CD40 ligand (e) or stimulated with BV6 in normal or conditioned medium at indicated concentrations (f) for 48 hr.…”
Section: Bv6 Induces Cell Death In Primary Cll Cells Irrespective Of mentioning
confidence: 99%
“…Molecular genetics characterization, including the detection of genomic aberrations by fluoresence in situ hybridization and the determination of IgVH status by sequencing, as well as the determination of ZAP-70 expression were performed as previously described. 5,19 …”
Section: Samples From Patients With Cllmentioning
confidence: 99%
“…1 Although several novel therapeutic approaches have entered the clinic and show high response rates in patients with CLL, most of them do not prolong overall survival, 2,3 which strongly depends on a number of prognostic factors. 4,5 Therefore, novel therapeutic options are desirable, especially for patients bearing negative prognostic markers such as cytogenetic aberrations (del17p and del11q), 6 unmutated IgVH gene status 7 or high ZAP-70 expression. 8 The clinical course of disease is heterogeneous.…”
Section: Introductionmentioning
confidence: 99%